2018
DOI: 10.3389/fimmu.2018.02339
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Immune Checkpoint Molecules to Eliminate Latent HIV

Abstract: The advent of antiretroviral therapy (ART) has seen a dramatic decrease in the morbidity and mortality of individuals infected with human immunodeficiency virus (HIV). However, ART is not curative and HIV persists in treated individuals within a pool of infected CD4+ memory T cells. The targeting and elimination of these cells, termed the latent HIV reservoir, may be essential in establishing a cure for HIV. Current HIV reservoir research is focused on identifying cells that harbor latent, replication-competen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…To examine the viral reservoir decay dynamics of the three groups, we assessed levels of cell-associated HIV DNA (17,18), HIV specific antibodies (19,20), and PD-1 expression on CD4 T-cells (21)(22)(23)(24) in this study.…”
Section: Dynamics Of Viral Reservoir During Artmentioning
confidence: 99%
“…To examine the viral reservoir decay dynamics of the three groups, we assessed levels of cell-associated HIV DNA (17,18), HIV specific antibodies (19,20), and PD-1 expression on CD4 T-cells (21)(22)(23)(24) in this study.…”
Section: Dynamics Of Viral Reservoir During Artmentioning
confidence: 99%
“…During chronic viral infections, including HIV infection, upregulation of inhibitory checkpoint molecules on immune cells contributes to T-cell exhaustion characterized by loss of effector functions and failure to proliferate in response to antigen (67). Checkpoint molecules are enriched on the surface of HIV-infected CD4 ϩ T cells in ART-treated individuals, and the number of cells expressing these molecules is tightly correlated with the size of the T-cell viral reservoir (68)(69)(70).…”
Section: Novel Directions In Hiv Cure Strategiesmentioning
confidence: 99%
“…One such method utilizes the relatively new discovery that exhausted CD4 T cells expressing immune checkpoint (IC) makers such as PD1 and CTLA-4, are a major reservoir of replication competent provirus (Banga et al, 2016;Fromentin et al, 2016;Castellano et al, 2017;McGary et al, 2017). IC markers are inhibitory receptors expressed by T cells in response to chronic viral infection to attenuate their effector function and limit tissue damage associated with long term immune activation (Boyer and Palmer, 2018). Cells expressing these markers, that are enriched in latent provirus, could therefore be specifically targeted for drug delivery or clearance using PD1, CTLA-4, or PD-L1 antibodies (Pantaleo and Levy, 2016;Gay et al, 2017a;Boyer and Palmer, 2018).…”
Section: Novel Cure Strategiesmentioning
confidence: 99%
“…IC markers are inhibitory receptors expressed by T cells in response to chronic viral infection to attenuate their effector function and limit tissue damage associated with long term immune activation (Boyer and Palmer, 2018). Cells expressing these markers, that are enriched in latent provirus, could therefore be specifically targeted for drug delivery or clearance using PD1, CTLA-4, or PD-L1 antibodies (Pantaleo and Levy, 2016;Gay et al, 2017a;Boyer and Palmer, 2018). To this end, several studies have demonstrated that IC blockade can inhibit the establishment of latency in vitro and aid latency reversal in vivo, revealing its potential as an HIV-1 therapeutic (McManamy et al, 2014;Gay et al, 2017a;Evans et al, 2018;Fromentin et al, 2019;van der Sluis et al, 2020).…”
Section: Novel Cure Strategiesmentioning
confidence: 99%